P‐31: A Statistical Paradigm for Assessment of Subjective Image Quality Results. Issue 1 (30th May 2018) - Cutone, Matthew D.; Dalecki, Marc; Goel, James; Wilcox, Laurie M.; Allison, Robert S.
Abstract : ISO/IEC 29170‐2 outlines a subjective procedure for assessing codec quality for near‐threshold artifacts. Here we outline a statistical method for analyzing these data using Generalized Linear Mixed‐Models (GLMMs). This procedure provides insightful metrics concerning the relative performance of two or more codecs that may aid in the perceptually‐guided development and selection of novel codec technologies.